2016
DOI: 10.1371/journal.pntd.0004811
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Immunity Induced by Persistent Leishmania major Does Not Preclude Secondary Re-Infection: Implications for Genetic Exchange, Diversity and Vaccination

Abstract: BackgroundMany microbes have evolved the ability to co-exist for long periods of time within other species in the absence of overt pathology. Evolutionary biologists have proposed benefits to the microbe from ‘asymptomatic persistent infections’, most commonly invoking increased likelihood of transmission by longer-lived hosts. Typically asymptomatic persistent infections arise from strong containment by the immune system, accompanied by protective immunity; such ‘vaccination’ from overt disease in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…Although we have not evaluated the parasitic load in the draining lymph nodes, it is known that even in cured animals the persistence of parasites in the draining lymph node occurs for long periods. The persistence of parasites seems to be important for the maintenance of the cellular immune response and generation of T cell memory (Mandell and Beverley, 2016; Conceição-Silva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not evaluated the parasitic load in the draining lymph nodes, it is known that even in cured animals the persistence of parasites in the draining lymph node occurs for long periods. The persistence of parasites seems to be important for the maintenance of the cellular immune response and generation of T cell memory (Mandell and Beverley, 2016; Conceição-Silva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“… Stenger et al (1996) showed the reactivation of latent leishmaniasis by inhibition of inducible nitric oxide synthase in mice experimentally infected with L. major . However, recently two populations: one rapidly replicating, like parasites in acute infections, and another showing little evidence of replication were demonstrated in the persistent infection by L. major ( Mandell and Beverley, 2016 , 2017 ). The persistent parasite were found residing in macrophages and DCs expressing inducible nitric oxide synthase (iNOS), instead of “safe” immunoprivileged cell types, suggesting that some populations of Leishmania may be resistant to NO ( Mandell and Beverley, 2017 ).…”
Section: Parasite Persistencementioning
confidence: 99%
“…Second, they pose a substantial risk to infected people in the event of immunosuppression, as the persistent parasites can "reactivate," leading to severe disease (17). Finally, they maintain protective immunity to subsequent Leishmania infections through concomitant immunity, which results in amelioration of disease pathology without sterilization of either the persistent or incoming parasite (18,19). Indeed, healed Leishmania infections are the gold standard in anti-Leishmania immunity, and to date no other vaccination approaches have proven as successful in humans (18).…”
mentioning
confidence: 99%